Inhalable Polymeric Micro and Nano-immunoadjuvants for Developing Therapeutic Vaccines in the Treatment of Non-small Cell Lung Cancer - Dondulkar, Ayusha; Akojwar, Natasha; Katta, Chanti; Khatri, Dharmendra K.; Mehra, Neelesh K.; Singh, Shashi B.; Madan, Jitender (Current Pharmaceutical Design, 2022)
Non-small cell lung cancer (NSCLC) is a leading cause of death in millions of cancer patients. Lack of diagnosis at an early stage in addition to no specific guidelines for its treatment, and a higher rate of treatment- related toxicity further deteriorate the conditions. Current therapies encompass surgery, chemotherapy, radiation therapy, and immunotherapy according to the pattern and the stage of lung cancer. Among all, with a longlasting therapeutic action, reduced side-effects, and a higher rate of survival, therapeutic cancer vaccine is a new, improved strategy for treating NSCLC. Immunoadjuvants are usually incorporated into the therapeutic vaccines to shield the antigen against environmental and physiological harsh conditions in addition to boosting the immune potential. Conventional immunoadjuvants are often associated with an inadequate cellular response, poor target specificity, and low antigen load. Recently, inhalable polymeric nano/micro immunoadjuvants have exhibited immense potential in the development of therapeutic vaccines for the treatment of NSCLC with improved mucosal immunization. The development of polymeric micro/nano immunoadjuvants brought a new era for vaccines with increased strength and efficiency. Therefore, in the present review, we explained the potential application of micro/nano immunoadjuvants for augmenting the stability and efficacy of inhalable vaccines in the treatment of NSCLC. In addition, the role of biodegradable, biocompatible, and non-toxic polymers has also been discussed with case studies.
Keywords: adenocarcinomas